Liquid crystals of hard rectangles on flat and cylindrical manifolds. Issue 7 (6th February 2018) - Sitta, Christoph E.; Smallenburg, Frank; Wittkowski, Raphael; Löwen, Hartmut
Abstract : The self-assembly of rectangular particles on flat and curved substrates was investigated using density functional theory and simulations. Abstract : Using the classical density functional theory of freezing and Monte Carlo computer simulations, we explore the liquid-crystalline phase behavior of hard rectangles on flat and cylindrical manifolds. Moreover, we study the effect of a static external field which couples to the rectangles' orientations, aligning them towards a preferred direction. In the flat and field-free case, the bulk phase diagram involves stable isotropic, nematic, tetratic, and smectic phases depending on the aspect ratio and number density of the particles. The external field shifts the transition curves significantly and generates a binematic phase at the expense of the tetratic phase. On a cylindrical manifold, we observe tilted smectic-like order, as obtained by wrapping a smectic layer around a cylinder. We find in general good agreement between our density functional calculations and particle-resolved computer simulations and mention possible setups to verify our predictions in experiments.